The Influence of Organizational Commitment and Organizational Culture on Accounting Fraud with Good Corporate Governance as a Moderating Variable - Pangaribuan, Grace Adelina; Pangaribuan, Glori Anastasya (Journal of Management and Digital Business, 2025)
Objective – This study aims to obtain empirical evidence Zon the Influence of Organizational Commitment and Organizational Culture on Accounting Fraud with Good Corporate Governance as a moderating variable. Design/methodology/approach – This study uses a primary research type. This study was conducted using a questionnaire distributed to employees working in government agencies Diskominfostandi and Disdik in Bekasi City, namely 50 questionnaires. Each questionnaire distributed contained 60 statements to be answered by respondents. From the distribution of questionnaires carried out, 50 respondents provided answers. To obtain the results of this study, the researcher used PLS SEM Version 3.0. Findings - Understanding organizational commitment has a positive but insignificant effect on accounting fraud, organizational culture has a positive but insignificant effect on accounting fraud, organizational commitment does not strengthen the relationship between good corporate governance and Accounting Fraud and Organizational Culture does not strengthen the relationship between Good Corporate Governance and Accounting Fraud. Originality/value - This study focuses on accounting fraud and this study is a unique and rarely found study, where the relationship between organizational commitment does not strengthen the relationship between good corporate governance and accounting fraud and organizational culture does not strengthen the relationship between good corporate governance and job satisfaction.